Apparent Missense Variant in COL7A1 Causes a Severe Form of Recessive Dystrophic Epidermolysis Bullosa via Effects on Splicing - Syed Ashraf Uddin; Nicole Cesarato; Aytaj Humbatova; Axel Schmidt; Fazal urRehman; Muhammad Naeem; Abdul Samad Tareen; Sabrina Wolf; Muhammad Anwar Panezai; Holger Thiele; Abdul Wali; Regina Fölster-Holst; et al. (Acta Dermato-Venereologica, 2020)

(untitled)
Dystrophic epidermolysis bullosa is an inherited skin disorder characterized by fragile skin that is prone to blistering. We report here a consanguineous Pakistani family with two siblings, in whom a severe recessive dystrophic epidermolysis bullosa was suspected. Using whole-exome sequencing for one sibling, the homozygous base substitution c.7249C>G in COL7A1 was identified, and could be confirmed in the other sibling by Sanger sequencing. In our exome data, this mutation was annotated as a missense substitution (p.Gln2417Glu), but in silico tools indicated a possible effect on splicing. Using the ExonTrap vector it was verified that the mutation leads to activation of a cryptic donor splice site, which leads to loss of 26 nucleotides, and a frameshift event predicted to result in a truncated protein (p.Q2417Sfs*57). The present report describes an apparent COL7A1 missense substitution with an unexpected consequence on splicing that leads to a severe recessive dystrophic epidermolysis bullosa phenotype.